Government of American colonies - Hawkinson, Clarence L. (My University, 1906)
Introduction: At the time of the Declaration of Independence the United States of America consisted of thirteen small states, occupying a narrow strip of land along the Atlantic ocean; but it was not long before territories were added in rapid succession to the original states; until our nation extended from the shores of the Atlantic on the east, to these of the Pacific on the west. Even then the growth of our country did not cease and where today we find one of the greatest and strongest nations of the world; not much over a century ago there was a complete wilderness, inhabited mostly by savages. The remarkable growth of our country is due, largely, to the establishment of an efficient government. It is the object of the writer to give a short explanation of how the territories were governed before having reached a stage of development necessary in order to become a state and placed on an equal basis with the original states. Secondly to show how the colonial possessions of the United States are now governed. The territory laying east of the Mississippi river, reaching as for south as the Spanish Floridas and north to the great lakes was acquired during the war for independence. So at the very beginning of our history the question of how to govern territories came up before Congress; which solved the problem with the Ordinance of 1787; this provided for the Government of the territory northwest of the Ohio river, which now constitutes five of our large states; namely, Ohio, Indiana, Illinois, Wisconsin and Michigan.
Citation: Hawkinson, Clarence L. Government of American colonies. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: History; Government; American Colonies; Theses